Systemic inflammation is associated with differential neural reactivity and connectivity to affective images. Issue 10 (14th May 2020) - Alvarez, Gabriella M; Hackman, Daniel A; Miller, Adam Bryant; Muscatell, Keely A
Abstract: Systemic inflammation is increasingly appreciated as a predictor of health and well-being. Further, inflammation has been shown to influence and be influenced by affective experiences. Although prior work has substantiated associations between inflammatory and affective processes, fewer studies have investigated the neurobiological correlates that underlie links between systemic, low-grade inflammation and affective reactivity. Thus, the current study examined whether markers of systemic inflammation (i.e. interleukin-6, C-reactive protein) are associated with differential patterns of neural activation and connectivity in corticolimbic regions in response to affective images. We investigated this question in a sample of 66 adults (44 women, M age = 54.98 years, range = 35–76) from the Midlife in the United States study. Higher levels of inflammation were associated with lower activity in limbic regions (i.e. amygdala, hippocampus, anterior insula, temporal pole) when viewing positive ( vs neutral) images. Higher levels of inflammation were also associated with greater connectivity between the hippocampus and the medial prefrontal cortex in response to positive images. Inflammatory markers were not associated with significant differences in activation or connectivity to negative images. These findings highlight the utility of health neuroscience approaches in demonstrating that physiological processes such as inflammation are related to how our brains respond to affective information.